Colorectal cancer statistics, 2023 - Siegel, Rebecca L.; Wagle, Nikita Sandeep; Cercek, Andrea; Smith, Robert A.; Jemal, Ahmedin (CA: a cancer journal for clinicians, 2023)
Colorectal cancer (CRC) is the second most common cause of cancer death in the United States. Every 3 years, the American Cancer Society provides an update of CRC statistics based on incidence from population‐based cancer registries and mortality from the National Center for Health Statistics. In 2023, approximately 153,020 individuals will be diagnosed with CRC and 52,550 will die from the disease, including 19,550 cases and 3750 deaths in individuals younger than 50 years. The decline in CRC incidence slowed from 3%–4% annually during the 2000s to 1% annually during 2011–2019, driven partly by an increase in individuals younger than 55 years of 1%–2% annually since the mid‐1990s. Consequently, the proportion of cases among those younger than 55 years increased from 11% in 1995 to 20% in 2019. Incidence since circa 2010 increased in those younger than 65 years for regional‐stage disease by about 2%–3% annually and for distant‐stage disease by 0.5%–3% annually, reversing the overall shift to earlier stage diagnosis that occurred during 1995 through 2005. For example, 60% of all new cases were advanced in 2019 versus 52% in the mid‐2000s and 57% in 1995, before widespread screening. There is also a shift to left‐sided tumors, with the proportion of rectal cancer increasing from 27% in 1995 to 31% in 2019. CRC mortality declined by 2% annually from 2011–2020 overall but increased by 0.5%–3% annually in individuals younger than 50 years and in Native Americans younger than 65 years. In summary, despite continued overall declines, CRC is rapidly shifting to diagnosis at a younger age, at a more advanced stage, and in the left colon/rectum. Progress against CRC could be accelerated by uncovering the etiology of rising incidence in generations born since 1950 and increasing access to high‐quality screening and treatment among all populations, especially Native Americans.